Exploring Gender Differences in Middle School Students’ Creative Approaches to Open-Ended Geometry Problems - Latifah Nuryah; Budayasa, I Ketut; Lukito, Agung (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Creativity is an important skill in 21st century education. Student creativity can be measured, among other things, through open-ended questions. Gender differences are one factor that influences creativity. The difference between masculine male creativity and feminine female creativity has always been a subject of debate. Researchers measured how female and male students' creativity in solving open-ended geometry problems. In this study, feminine female students showed greater flexibility, as evidenced by their work, which included six variations of solutions. Male students showed novelty, as evidenced by new variations of solutions according to junior high school students. This study supports research that states that there are differences between the creativity of female and male students in solving open-ended problems.